CLINICAL CASE OF BIOTINIDASE DEFICIENCY - Yunusova, M.R.; Rakhimbaeva, G.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Biotinidase deficiency is an autosomal recessively inherited metabolic disease. If left untreated, patients with biotinidase deficiency typically develop neurological and skin symptoms that can lead to coma and death. This article examined a clinical case of a patient with biotinidase deficiency. The article is aimed at increasing the attention of neurologists to the possible causes of symptomatic epilepsy against the background of a hereditary autosomal recessive metabolic disease - biotinidase deficiency.